Risk Factors and Types of Urinary Incontinence among Middle-Aged and Older Male and Female Primary Care Patients in Kaunas Region of Lithuania: Cross Sectional Study - Aniuliene, Rosita; Aniulis, Povilas; Steibliene, Vesta (Urology Journal, 2016)
Purpose: The aims of the study were to evaluate the incidences, types of urinary incontinence (UI) and its risk factors among middle-aged and older (> 40 years) men and women visiting a general practitioner (GP). Materials and Methods. This is a descriptive and cross-sectional comparative study using a questionnaire-based survey included 172 male and female patients who consecutively visited a primary care center in Kaunas region of Lithuania. Results: All 86 women (100%) and 65 men (75.58%) had symptoms of UI (P < .001). About 55% of women were classified as having stress urinary incontinence (SUI) and 60% of men urge urinary incontinence (UUI) (P < .001). The risk factors for women with SUI were: age below 60 years (odds ratio [OR] = 2.89, 95% confidence interval [CI]: 1.89-4.43; P < .001), being married (OR = 6.31, 95% CI: 2.35-16.97; P < .001), sedentary-standing job (OR = 1.492, 95% CI: 1.01-2.20; P = 0.041), arterial hypertension (OR = 2.03, 95% CI: 1.39-2.96: P < .001), diabetes mellitus (OR = 3.01, 95% CI: 1.02-8.86; P = .032), menopause (OR = 1.48, 95% CI: 1.20-1.83; P < .001) and features of past pregnancies. The UUI was associated with age over 60 years (OR in men = 2.93, 95% CI: 1.15-7.51; P = .022, in women OR = 8.76, 95% CI: 2.37-32.33; P < .001. Low health-related quality of life was the most prevalent among men with UUI (50.8%) and among women with SUI (23.3%) (P = .023). Conclusion: UI was common among patients aged > 40 years visiting GP and affected more women of the same age range. SUI was more prevalent among women, while more men had UUI. Age below 60, being married, pregnancy and delivery history, concomitant illnesses were significant risk factors for women’ SUI and older age and menopause for UUI. The only risk factor for men’ UUI was age over 60 years.